Fashion and cities: a relationship that designs future scenarios (Revista de Ensino em Artes, Moda e Design, 2023)
Interview carried out by the editors of the Revista de Ensino em Artes, Moda e Design to GT Fashion, Cities and Future Scenarios.
Keywords: future; scenarios; cities; fashion